Player readiness scores correlate to changes in spatiotemporal gait in the presence of fatigue in women's soccer players - Jaskowak, D.; Lewis, M.; Rizzuto, S.; Williams, J. (The Journal of Strength and Conditioning Research, 2021)
Wearable technology incorporating accelerometry is a widely used component of athlete monitoring. Various methods of gait assessment using accelerometers have been developed for clinical settings. Alterations in various gait characteristic can be indicative of pathology or fatigue. Therefore, monitoring gait in athletes could provide insight into the development of acute or chronic fatigue throughout the season. Purpose: The purpose of this study was to determine if spatiotemporal gait variables describe acute changes in player readiness and fatigue. Methods: Gait variables were calculated and tracked for a full season of a NCAA D1 women's soccer program using a trunk mounted GPS embedded accelerometer (STATSports APEX, 18 Hz GPS, 100 Hz accelerometer). At the start of each home training session, gait variables were collected during an easy jog around the practice fields (~400 m). Player readiness scores (10 point scale) were also collected during each session. Gait variables were observed each week, starting with the session following the NCAA required off day. An algorithm was developed using accelerometer and GPS signals and event detection via Gaussian continuous wavelet transform which determined foot contact times step and stride times and lengths. Results: While a longitudinal analysis of gait variables showed no linear trend across the season, there were significant changes in spatiotemporal variables within the training week. As running speed increases, time variables typically decrease. However, there we numerous weeks during which time variables did not decrease in response to increases in speed and step length. This trend was particularly evident between days when player readiness scores were significantly poorer. Conclusions: Within-season fluctuations in gait suggests a more complex pattern of workload and fatigue. Poorer player readiness scores were correlated to a change in spatiotemporal gait characteristics, particularly time variables. Practical Applications: The results of this study suggests that changes in spatiotemporal gait variables may be sensitive enough to be able to track acute changes in training load and reflects player readiness. Thus, they offer a potential metric for day to day training load and fatigue evaluation.